Merchandising in the Trading Enterprise Management System - Shymko Olha V. (Bìznes Inform, 2020)
The article is concerned with solving the theoretical, methodological and applied issues of the use of merchandising in the activities of trading enterprises in the face of increasing competition in the Ukrainian consumer market and the activization of global transformational processes. The economic essence and purpose of merchandising are disclosed, its classification features and types are defined. The motives behind the use of merchandising in the activities of trading enterprises are described. Merchandising as a specific marketing technology is considered in the context of functional zones, which play a specific role in interaction with consumers. The influence of individual elements of the merchandising system on the formation of alleged consumer behavior in the trading hall is characterized. The peculiarities of consumers’ perception of the merchandising space are analyzed. The factors that cause discomfort of perception of goods in the store are allocated. The main tasks of managing the levels and instruments of merchandising, the solution of which will allow a retail company to respond quickly to changes in market conditions and optimally combine the goals and objectives of commercial activity with the consumers’ needs, are defined.